2011
DOI: 10.1007/s11255-011-0085-9
|View full text |Cite
|
Sign up to set email alerts
|

Charlson comorbidity score is a strong predictor of mortality in hemodialysis patients

Abstract: Purpose The Charlson comorbidity index (CCI) is a commonly used scale for assessing morbidity, but its role in assessing mortality in hemodialysis patients is not clear. Age, a component of CCI, is a strong risk factor for morbidity and mortality in chronic diseases and correlates with comorbidities. We hypothesized that the Charlson comorbidity index without age is a strong predictor of mortality in hemodialysis patients. Methods A 6-year cohort of 893 hemodialysis patients was examined for an association b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
61
0
5

Year Published

2014
2014
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 90 publications
(72 citation statements)
references
References 41 publications
5
61
0
5
Order By: Relevance
“…Unfortunately, this clinical patient care database did not have bone turnover marker data for analysis in this adherent population. Some authors have suggested that a persistent osteoporotic T-score indicates patients at higher fracture risk, who might not be candidates for drug holidays [23]. Similarly some authors have proposed considering a BMD target (such as achieving a non-osteoporotic T-score) as a hypothetical goal of treatment [9], based on the finding that persistent BMD Tscores less than -2.5 after treatment with alendronate indicated a higher risk of subsequent fracture in the FLEX trial [14].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Unfortunately, this clinical patient care database did not have bone turnover marker data for analysis in this adherent population. Some authors have suggested that a persistent osteoporotic T-score indicates patients at higher fracture risk, who might not be candidates for drug holidays [23]. Similarly some authors have proposed considering a BMD target (such as achieving a non-osteoporotic T-score) as a hypothetical goal of treatment [9], based on the finding that persistent BMD Tscores less than -2.5 after treatment with alendronate indicated a higher risk of subsequent fracture in the FLEX trial [14].…”
Section: Discussionmentioning
confidence: 99%
“…The Charlson Comorbidity Index is generated from ICD9 codes to categorize burden of comorbidities. A higher score on the Charlson Comorbidity index indicates greater number or degree of comorbidities and is a predictor for mortality or for complications in a variety of disease states [22,23]. In addition codes for other major disease groups and selected conditions that may affect bone metabolism or risk of falls were also collected.…”
Section: Covariatesmentioning
confidence: 99%
“…37,38 The CCI was calculated using Quan's Enhanced ICD-9-CM 39 and then categorized into 5 groups; 2 (renal disease only), 3 to 4, 5, 6, and 7 or more. 40 Patients who had diabetic nephropathy as the primary kidney disease were considered to have diabetes with chronic complications.…”
Section: Methodsmentioning
confidence: 99%
“…Covariates in all models consisted of age, sex, HD vintage, BMI, serum albumin level, and CCI. We used CCI (except renal disease), as it includes all comorbidities and has been validated in several studies as a good predictor of mortality in HD patients (14,15).…”
Section: Methodsmentioning
confidence: 99%